(untitled) (BIS Humanities and Social Science, 2026)
This research aims to analyze Sukma Widi Margaretta’s personal branding strategy through her Instagram account @sukmamargaretta in shaping her public image as a mountaineering influencer. This phenomenon is relevant to increasing popularity of social media as a medium of self-identity and lifestyle representation, especially in outdoor activities which are now widely displayed in visual and narrative formats by influencers. As a female climber, Sukma not only represents courage and resilience in conquering nature, but also presents an educative, reflective and authentic narrative that distinguishes her from other climbing influencers. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews with Sukma and her teams and visual documentation from Sukma’s Instagram account, and involves three active followers as supporting informants. The results showed that Sukma managed to build a consistent and strong personal branding through voice differentiation, narrative style, and emphasis on safety and ecological values. Her strategy not only impacts the formation of a positive public image, but also contributes to the empowerment of women in the digital realm as well as the preservation of natural culture through social media. This research confirms the importance of ethics and responsibility in digital communication practices and encourages media literacy so that the public can respond to visual content with a critical and reflective attitude, without getting caught up in the romanticization of high-risk activities such as tourism mountain climbing.